A novel-16–60 V input common-mode voltage current-shunt monitor. (January 2023) - Duan, Quanzhen; Duan, Ying; Kong, Dameng; Li, Liwei; Huang, Shengming
Abstract: This paper presents an effective design solution for current-shunt monitor (CSM) adapting to both positive and negative power supply applications, where the supply voltage is input common-mode voltage (CMV) of CSM ranged from − 16 to 60 V. The proposed CSM mainly consists of a high-voltage low-drop output (HVLDO) regulator, a CSM core, and a 2nd-stage gain generator. The HVLDO regulator converts the independent supply voltage (5-16 V) to a stable internal output supply voltage of 5 V for other consequent circuits. The proposed CSM core adopts a fully-differential amplifier, a single-ended output amplifier, current-mirror transistors, and several resistors to constitute a stable negative feedback system. Due to its stable operation, the CSM core with both positive and negative CMV can successfully detect drops across the shunt resistor. The 2nd-stage generator is used to achieve a higher gain. By selecting proper transistor and resistor size in both CSM core and 2nd-stage gain generator, a total scaled gain of 100 V/V is achieved in this study. The proposed CSM architecture has been successfully implemented in a 0 . 25 μ m Bipolar-CMOS-DMOS (BCD) technology, and the area is around 1.44 mm 2 . Measurements show that the proposed CSM with an input CM voltage ranged from -16–60 V can sense an input voltage difference 4–16 mV.